Habitual choice strategy, poverty and urban consumer demand for biofortified iron beans - Oparinde, Adewale; Birol, Ekin; Murekezi, Abdoul (International Food Policy Research Institute, 2018)
Increasing urbanization in developing countries creates current and future challenges for the global food system to deliver high quality nutritious foods and provide equitable access for the urban poor. In this paper, we examine the role of habit, poverty and information in urban consumer demand for nutritious foods in the context of biofortified iron beans as a public health intervention in Africa. We used an experimental auction-like technique (Becker-DeGroot-Marschak mechanism) to elicit consumer willingness to pay (WTP) for the nutritional value of iron beans. The provision of information on the nutritional value of iron translates into significant premiums (13 – 15%) for the iron bean varieties while habit has no significant impact. Eliminating participatory fees, as was done in this study, provides an alternative practical approach for identifying ‘hypothetical bias’ in value elicitations. Results suggest that WTP can be inflated by about 7% when participants have ex ante intentions not to pay out of pocket after getting an opportunity to buy a product in the auction-like experiment. We found that poverty plays a significant role in consumer demand. There is a difference of about 11% in the price that consumers from poor households are willing to pay for an iron bean variety relative to the price that consumers from average households are willing to pay. These results have implications for designing effective and inclusive value chain approach to ensure that urban poor also benefit adequately from biofortification through an equitable pricing system.